Emergence of KPC-113 and KPC-114 variants in ceftazidime-avibactam-resistant Klebsiella pneumoniae belonging to high-risk clones ST11 and ST16 in South America - Vásquez Ponce, Felipe (2023)
Two novel variants of Klebsiella pneumoniae carbapenemase (KPC) associated with resistance to ceftazidime-avibactam (CZA) and designated as KPC-113 and KPC-114 by NCBI were identified in 2020, in clinical isolates of Klebsiella pneumoniae in Brazil. While K. pneumoniae of ST16 harbored the blaKPC-113 variant on an IncFII-IncFIB plasmid, K. pneumoniae of ST11 carried the blaKPC-114 variant on an IncN plasmid. Both isolates displayed resistance to broad-spectrum cephalosporins, β-lactam inhibitors, and ertapenem and doripenem, whereas K. pneumoniae producing KPC-114 showed susceptibility to imipenem and meropenem. Whole-genome sequencing and in silico analysis revealed that KPC-113 presented a Gly insertion between Ambler positions 264 and 265 (R264_A265insG), whereas KPC-114 displayed two amino acid insertions (Ser-Ser) between Ambler positions 181 and 182 (S181_P182insSS) in KPC-2, responsible for CZA resistance profiles. Our results confirm the emergence of novel KPC variants associated with resistance to CZA in international clones of K. pneumoniae circulating in South America. IMPORTANCE KPC-2 carbapenemases are endemic in Latin America. In this regard, in 2018, ceftazidime-avibactam (CZA) was authorized for clinical use in Brazil due to its significant activity against KPC-2 producers. In recent years, reports of resistance to CZA have increased in this country, limiting its clinical application. In this study, we report the emergence of two novel KPC-2 variants, named KPC-113 and KPC-114, associated with CZA resistance in Klebsiella pneumoniae strains belonging to high-risk clones ST11 and ST16. Our finding suggests that novel mutations in KPC-2 are increasing in South America, which is a critical issue deserving active surveillance.